2017
DOI: 10.1136/bmjsem-2016-000180
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of injuries in the Spanish national futsal male team: a five-season retrospective study

Abstract: BackgroundFutsal started being played in 1930 and the number of futsal players has increased all over the world ever since. Nonetheless, despite the fact that Spain is one of the most relevant national teams worldwide, information on the incidence of injuries and their anthropometric characteristics is sparse in this country.AimTo analyse medical assistance provided to players in their prematch concentration camps with the Spanish national team over five seasons, from 2010–2011 to 2014–2015, and also to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
4
23
0
2
Order By: Relevance
“…An assessment method to monitor body mass status was body mass index (BMI), which has been used to categorize humans as underweight, normal weight, overweight, and obese for health purposes. BMI was included in several physical fitness batteries administered to futsal players [3,4,10,11]. Nevertheless, the relationship of BMI with other physical fitness components has not been examined in futsal so far.…”
Section: Introductionmentioning
confidence: 99%
“…An assessment method to monitor body mass status was body mass index (BMI), which has been used to categorize humans as underweight, normal weight, overweight, and obese for health purposes. BMI was included in several physical fitness batteries administered to futsal players [3,4,10,11]. Nevertheless, the relationship of BMI with other physical fitness components has not been examined in futsal so far.…”
Section: Introductionmentioning
confidence: 99%
“…14 In futsal, prospective studies with hamstring injury rates are scarce, but Junge and Dvorak 10 demonstrated that thigh strain is among the most prevalent diagnoses of time-loss injuries in futsal players. In addition, recently Martinez-Rianza et al 15 analyzed medical assistance to Spanish national futsal team over five seasons and showed that in 43.3% of the cases, injuries were sustained in the thigh, followed by the leg (12.6%) and knee (10%). Most assistance cases (52.6%) were due to muscle overload (i.e., when the individual did not have an anatomical injury but the muscle was painful and slightly tight when manually explored) and 14.4% were due to residual pain.…”
Section: Introductionmentioning
confidence: 99%
“…Contact injuries were more frequent during matches than training, but similar to previous research in futsal [3,8,9] and soccer [24] only 25.6 % of all injuries were suffered by contact mechanisms. However, other studies reported higher values for contact injuries on female [1,2] and male [20] futsal teams. One explanation for the dissimilarity might be the regional differences in injury incidence observed in studies of other team sports or the different medical support according to the level of the teams.…”
Section: Discussionmentioning
confidence: 82%
“…Data were then categorized and codified to be analyzed with SPSS for Windows (20.0, Chicago, IL, USA), considering a significance level at p < 0.05. Qualitative variables were exposed by absolute frequency and percentages [20]. The overall injury incidence, match injury incidence and training injury incidence were the number of injuries divided by 1000 player-hours in total, match and training, respectively, including also 95 % confidence intervals (CI) following previous research about injury risk statistical approaches [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation